KAPABILITAS KERJA PEGAWAI, PROSEDUR KERJA, BUDAYA KERJA DAN KUALITAS PELAYANAN PUBLIK - ', Junaidi (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Employee Capability, Work Procedures, Work Culture and Quality of Public Services. This research study aims to determine and analyze the relationship between the variables of employee capabilities, work procedures, work culture with the quality of public services. Design research using quantitative research methods. The population is customers as much as 6204 and a sample of 100 people were taken by using the formula slovin. Data collection techniques using questionnaires and documentation. The analysis showed that the capability of employee, job procedures and work culture has a tendency to relatively weak positive relationship with the variable quality of public services. Thus the hypothesis statement “there is a positive relationship between employee capabilities, work procedures and work culture, quality of public services at the Regional Water Company (PDAM) Indragiri Hulu” either individually or simultaneously acceptable.